Visionary Leadership in Education: Strategies for Achieving International Standard - Hidayati, Nur; Muis, Abd; Ubaidillah, Ubaidillah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to analyze the strategies required to achieve international standard education through visionary leadership. This study employs a qualitative method with a case study approach, utilizing informant sources that include principals, academics, and teachers. Data were collected through interviews, observations, and documentation, with data analysis conducted using the Miles and Huberman model, which consists of three stages: data collection, data reduction, and data presentation. The study's results indicate that visionary leadership has successfully implemented modern educational approaches that meet international standards. The approach employs the International Collaborative Approach strategy, Leadership Focused on Curriculum Innovation, and development of 21st-century skills. This study provides important implications for the development of educational policies, particularly in the application of visionary leadership in schools that meet international standards. The results of this study can serve as a reference for principals and educators in designing educational strategies that are more effective, innovative, and capable of meeting global challenges in the 21st century.